Early-life conditioning strategies to reduce dietary phosphorus in broilers: underlying mechanisms. (2020) - Valable, A. S.; Létourneau-Montminy, M. P.; Klein, S.; Lardic, L.; Lecompte, F.; Metayer-Coustard, S.; Même, N.; Page, G.; Duclos, M. J.; Narcy, A.
Abstract: Chickens adapt to P and Ca restriction during the very first days of life by improving P utilisation efficiency. The present study was built to identify the mechanisms underlying this adaptive capacity, and to identify the optimal window of application of the restriction (depletion). A total of 1600 Cobb 500 TM male broilers were used. During each phase (from age 0 to 4 d, 5 to 8 d, 9 to 18 d and 19 to 33 d), the animals received either a control diet (H) or a restricted diet (L) with reduced levels of non-phytate P (nPP) and Ca (between −14 and −25 % for both) with four dietary sequences: HHHH, HLHL, LHHL and LLHL. None of the feeding strategies affected growth. Tibia ash content at day 4 and 8 was impaired when the L diet was fed from 0 to 4 and 5 to 8 d, respectively ( P = 0⋅038 and P = 0⋅005). Whatever the early restriction period or length between 0 and 8 d of age, the mineralisation delay was compensated by day 18. This was accompanied by an increased mRNA expression of the Ca transporter, CALB1, and an increased apparent ileal digestibility of Ca at day 8 ( P < 0⋅001). This adaptation was limited to the starter phase in restricted birds. No effect was seen on P transporters mRNA or protein expression. In conclusion, birds adapted to mineral restriction by increasing Ca and nPP utilisation efficiencies. Depletion−repletion strategies are promising in improving the sustainability of broiler production but need to be validated in phytase-supplemented diets.